HUBUNGAN INISIASI MENYUSU DINI (IMD) DENGAN KEBERHASILAN ASI EKSKLUSIF PADA BAYI USIA 6-12 BULAN DI PUSKESMAS MLATI II TAHUN 2017 - Lediana Sabu Sogen; Dwi Ratnaningsih (Politeknik Kesehatan Permata Indonesia Yogyakarta, 2017)
One effort to suppress Infant Mortality Rate is withas soon as possible givecolostrum to newborns.Effort to give Colostrum is done with early breastfeedinginitiation. Early breastfeeding initiation is a strong enabling factor for exclusivebreastfeeding. The percentage of exclusive breastfeeding in Indonesia in 2013 was54.3%, and Early breastfeeding initiation was 34.5%. Purpose: To determine thecorrelation of early breastfeeding initiation with exclusive breastfeeding in children atMlati II Health Center. Methods: The research is an analytic observational study withcross sectional design. The population is 250 and 41 sample using purposive samplingtechnique. The independent variable is early breasfeeding initiation. The dependentvariable is exclusive breastfeeding. Data collection using questionnaire and check listthat analyzied with chi square test. Result: 75,6% respondents did early breastfeedinginitiation, 24,4% respondents no early breastfeeding initiation and 61,0% respondentsgave exclusive breastfeeding, 39,0% no exclusive breastfeeding. There is a significantcorrelation between early breastfeeding initiation with exclusive breastfeeding (ρ =0.002 < 0,05) Conclusion: There are is a correlation between early breastfeedinginitiation with exclusive breastfeeding among children in Mlati IIHealth Center .